Test–Retest Reliability of Handgrip Strength Measurement in Children and Preadolescents - Jakub S. Gąsior (International Journal of Environmental Research and Public Health, 2020)
The reliability of handgrip strength (HGS) measurement has been confirmed in adults but has been sparsely addressed in pediatric populations. The aims of this study are twofold: to determine whether sex, age and/or hand-dominance influence the test–retest differences and to establish the reliability level of the HGS measurement in typical developing pediatric participants. A total of 338 participants aged 7–13 years were tested using a digital handgrip strength (HGS) dynamometer (Jamar Plus+ Dynamometer) by the same rater on two testing trials separated by a one-day interval between sessions. The HGS testing was conducted according to the American Society of Hand Therapists recommendations. Relative and absolute reliability statistics were calculated. Age influenced the test–retest difference of the HGS measurement as children compared to preadolescents had lower intraclass correlation coefficients (0.95 vs. 0.98), standard error of measurement (SEM) (0.74 vs. 0.78 kg), smallest detectable difference (SDD) (2.05 vs. 2.16 kg) and higher values of the percentage value of SEM (5.48 vs. 3.44%), normalized SDD (15.52 vs. 9.61%) and a mean difference between the test and retest values (0.50 vs. 0.02 kg) for the dominant hand. The results indicate that the protocol using the Jamar digital handgrip dynamometer is a reliable instrument to measure HGS in participants aged 7–13 years with typical development. Clinicians and researchers therefore can have confidence in determining the minimally clinical effect for HGS.